The Moyamoya disease - the description of clinical case = Choroba moyamoya - opis przypadku klinicznego - Woźniak, Kamila; Ratuszek-Sadowska, Dorota Małgorzata; Śniegocki, Maciej (Journal of Education, Health and Sport, 2015)
Woźniak Kamila, Ratuszek-Sadowska Dorota, Śniegocki Maciej. The Moyamoya disease - the description of clinical case = Choroba moyamoya - opis przypadku klinicznego. Journal of Education, Health and Sport. 2015;5(8):253-264. ISSN 2391-8306. DOI 10.5281/zenodo.28231 http://dx.doi.org/10.5281/zenodo.28231 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A253-264 https://pbn.nauka.gov.pl/works/608626 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 18.08.2015. The Moyamoya disease - the description of clinical case Choroba moyamoya - opis przypadku klinicznego Kamila Woźniak1, Dorota Ratuszek-Sadowska2, Maciej Śniegocki1 1. Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu, Polska Department of Neurosurgery, Neurotraumatology and Pediatric Neurosurgery Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland 2. Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu, Polska 2.Chair and Department of Rehabilitation Medicine, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Poland Streszczenie Choroba moyamoya (ang. moyamoya disease) jest to rzadki zespół chorobowy o nieznanej etiologii, występujący głównie u młodych Azjatów. Powoduje on niedrożność dużych tętnic wewnątrzczaszkowych - szczególnie końcowego odcinka tętnicy szyjnej wewnętrznej, tętnicy środkowej oraz przedniej mózgu. Konsekwencją niedrożności jest niedokrwienie ośrodkowego układu nerwowego, przebiegające najczęściej pod postacią przemijających napadów niedokrwiennych, choć może również przebiegać jako udar mózgu lub krwotok mózgowy. W języku japońskim moyamoya oznacza kłęby dymu. Słowa kluczowe: choroba moyamoya, angiografia, udar, TIA. Abstract Moyamoya disease is a rare syndrome of unknown etiology, occurring mostly in young Asians. It causes obstruction of large intracranial arteries - particularly the distal internal carotid artery and the artery middle and front of the brain. The consequence of ischemia is obstruction of the central nervous system, running most often in the form of transient ischemic attacks, although it can also occur as stroke or cerebral hemorrhage. In Japanese moyamoya means billows of smoke. Key words: moyamoya disease, angiography, stroke, TIA.